2019
DOI: 10.1186/s13033-019-0273-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of people detained within the justice system in Africa: systematic review and meta-analysis

Abstract: Worldwide, people with mental disorders are detained within the justice system at higher rates than the general population and often suffer human rights abuses. This review sought to understand the state of knowledge on the mental health of people detained in the justice system in Africa, including epidemiology, conditions of detention, and interventions. We included all primary research studies examining mental disorders or mental health policy related to detention within the justice system in Africa. 80 met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 88 publications
(126 reference statements)
1
20
0
Order By: Relevance
“…5%); the perception that the government has been unfair to them (24.7%); the conviction that nobody cared (19%); and anger and bitterness toward society (16.4%). The prevalence of depression (37.8%) as measured via the PhQ-9 screening tool is higher than the pooled prevalence of mood disorders in the African region (22%) [5]. However, it is similar to that reported by Armiya'u et al [9,10] in Jos (30.8%), but higher than the reported prevalence of depression of 20.8% in a similar prison population from Ibadan [17].…”
Section: Ethicssupporting
confidence: 52%
See 2 more Smart Citations
“…5%); the perception that the government has been unfair to them (24.7%); the conviction that nobody cared (19%); and anger and bitterness toward society (16.4%). The prevalence of depression (37.8%) as measured via the PhQ-9 screening tool is higher than the pooled prevalence of mood disorders in the African region (22%) [5]. However, it is similar to that reported by Armiya'u et al [9,10] in Jos (30.8%), but higher than the reported prevalence of depression of 20.8% in a similar prison population from Ibadan [17].…”
Section: Ethicssupporting
confidence: 52%
“…The authors called for more studies from prison populations in low-and middle-income countries (LMICs) [3]. Lovett et al's subsequent meta-analysis of prevalence studies among prison inmates in Africa specifically estimates the pooled prevalence of mood disorders to be 22% [5].…”
Section: Depression In Prisons Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…The metaanalysis conducted in 2019 by Lovett et al revealed that the prison population in sub-Saharan Africa consisted of men in proportions ranging from 93% to 100% [7]. The average ages fell primarily in the age group of 31 -37 years [7]. In our series, the accused are most commonly married (72%) individuals who did not receive formal education (59%).…”
Section: Discussionmentioning
confidence: 51%
“…In Nigeria, those charged with homicide are men in 93% of cases [6]. The metaanalysis conducted in 2019 by Lovett et al revealed that the prison population in sub-Saharan Africa consisted of men in proportions ranging from 93% to 100% [7]. The average ages fell primarily in the age group of 31 -37 years [7].…”
Section: Discussionmentioning
confidence: 99%